Popular culture in Indonesia [ fluid identities in post-authoritarian politics - Heryanto, Ariel (Abingdon, Oxon ; New York : Routledge, 2008)
This book examines popular culture in Indonesia, bringing material on Indonesia?s media and popular culture to an English readership for the first time. It includes analysis of important themes including citizenship, gender, class, age and ethnicity, showing how developments in Indonesian society more generally are inextricably linked to popular culture.
1. Pop Culture and competing identities -- 2. Indonesian cinema: Exploring cultures of masculinity, censorship and violence -- 3. Changing social formations in Indonesian and Thai teen movies -- 4. Citizenship and Indonesian ethnic Chinese in post-1998 films -- 5. Consuming Taiwanese boys culture: Watching Meteor Garden with urban Kampung women in Indonesia -- 6. Fame, fortune, Fantasi: Indonesian Idol and the new celebrity -- 7. Consuming gossip: A Re-domestication of Indonesian women -- 8. Television dreams: Simulation, for a new reality of Indonesia -- 9. Other worlds in Yogyakarta: From jatilan to electronic music
Description based on print version record
Includes bibliographical references and index
Keywords: Mass media -- Indonesia; Indonesia -- Popular culture